1977
DOI: 10.1111/j.1365-2230.1977.tb01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses in patients with chronic Trichophyton rubrum infections

Abstract: Summary Thirty‐five patients were studied who were infected with Trichophyton species. There was a marked reduction in the incidence of delayed hypersensitivity skin responses in Trichophyton rubrum infections (12%) as compared with those patients who were infected with other dermatophytes (75%). There was no difference in the extent of leukocyte migration in either of the clinical groups infected with Trichophyton rubrum but inhibition was demonstrated in patients infected with other Trichophyton species. Nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…They further obtained evi dence that type I hypersensitivity in atopic subjects antag onizes the effect of cellular immunity locally [21]. They concluded that deficient or compromised cellular immuni ty is a correlate of susceptibility to dermatophyte infec tions from a study of experimental dermatophytosis in naturally infected subjects [22], In vitro assays of T lym phocyte functions also demonstrated a deficiency of cellu lar immunity as well as a high incidence of atopy in indi viduals with chronic dermatophytosis [23][24][25], Another interesting point about the chronicity is the high incidence of palmoplantar infections [25] and that of T.rubrum infections [26]. both of which are associated with low in vitro T lymphocyte reactivity.…”
Section: Chronic Dermatophyte Infectionsmentioning
confidence: 95%
“…They further obtained evi dence that type I hypersensitivity in atopic subjects antag onizes the effect of cellular immunity locally [21]. They concluded that deficient or compromised cellular immuni ty is a correlate of susceptibility to dermatophyte infec tions from a study of experimental dermatophytosis in naturally infected subjects [22], In vitro assays of T lym phocyte functions also demonstrated a deficiency of cellu lar immunity as well as a high incidence of atopy in indi viduals with chronic dermatophytosis [23][24][25], Another interesting point about the chronicity is the high incidence of palmoplantar infections [25] and that of T.rubrum infections [26]. both of which are associated with low in vitro T lymphocyte reactivity.…”
Section: Chronic Dermatophyte Infectionsmentioning
confidence: 95%
“…The method used in the leucocyte migration inhibition test has already been described (Hay and Brostoff, 1977). The test was carried out in sterile plastic chambers and peripheral blood leucocytes were used.…”
Section: Methodsmentioning
confidence: 99%
“…The dermatophyte fungus Trichophyton elicits distinct skin test reactions in different individuals. Immediate hypersensitivity (IH) 3 responses are associated with chronic recurrent infections and the presence of serum IgG, and IgG4 Ab, in addition to IgE Ab, specific for Trichophyton Ags (7)(8)(9)(10). Furthermore, improvement of asthma symptoms in a subset of IH responders with late-onset asthma after treatment with the systemic antifungal fluconazole has provided convincing evidence for the role of Ags derived from Trichophyton in allergic disease (11).…”
Section: Haracterization Of Distinct Cd4mentioning
confidence: 99%